DIGITAL HEALTH INTERVENTIONS IN TYPE 2 DIABETES: A NARRATIVE REVIEW OF PATIENT ENGAGEMENT, SELF-MANAGEMENT, AND BARRIERS TO ADOPTION - Anna Maria Kowalska; Aleksandra Kuls; Aleksandra Zofia Sobol; Bogusław Pabis; Justyna Maria Wiktorowicz; Martyna Kadłubańska; Nicole Bulińska; Zofia Sinczak; Sonia Zembrzuska; Stanisław Bajerski (International Journal of Innovative Technologies in Social Science, 2026)
Research objective: The aim of this paper was to present the role of digital health interventions in the treatment of type 2 diabetes, with a particular focus on their impact on patient engagement, self-management, clinical outcomes, and barriers related to their implementationMethods: This study was conducted as a narrative review. The literature search was performed using PubMed and Google Scholar databases. Articles published between 2020 and 2026 were included, with priority given to systematic reviews, meta-analyses, and selected original studies concerning adult patients with type 2 diabetes.Results: Digital health interventions can improve glycemic control, with the most consistent effect being a reduction in glycated hemoglobin (HbA1c). They also support patient engagement and self-management by facilitating regular monitoring, improving adherence, and promoting healthier behaviors. The most effective interventions were those combining data monitoring with feedback and professional support. At the same time, several barriers to implementation were identified, including limited digital literacy, technological usability issues, costs, access inequalities, and insufficient integration with healthcare systems.Conclusion: Digital health interventions represent a valuable supplement to type 2 diabetes treatment. Their effectiveness depends not only on the technology itself, but also on the quality of implementation, integration with medical care, and adaptation to patients’ individual needs.